2019
DOI: 10.33369/jvk.v2i1.10652
|View full text |Cite
|
Sign up to set email alerts
|

Derajat Stres Ibu Hamil Dan Preeklamsia Mempengaruhi Kejadian Persalinan Prematur

Abstract: ABSTRAK                                   Prematuritas menjadi penyebab sekitar 60%-80% kematian neonatus secara global. Penelitian ini bertujuan untuk melihat hubungan faktor stres pada ibu hamil dan preeklamsia dengan kejadian persalinan prematur. Penelitian ini adalah penelitian kuantitatif dengan desain studi kasus kontrol. Sampel sebanyak 152 orang diamana 62 orang ibu bersalin prematur dan 90 orng ibu bersalin aterm. Data dikumpulkan dengan consecutive sampling dan dianalisis menggunakan uji Chi Square. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…While for PE, Pragitara et al [30] and Saleha et al [31] also found similar results, showing that the value of pre-eclampsia to preterm birth was 2.5 (95%CI 1.34-4.83) and 6.9 (95%CI 1.874-25.849), respectively. Many studies state that preterm birth is a consequence of multifactorial factors.…”
Section: Discussionmentioning
confidence: 64%
“…While for PE, Pragitara et al [30] and Saleha et al [31] also found similar results, showing that the value of pre-eclampsia to preterm birth was 2.5 (95%CI 1.34-4.83) and 6.9 (95%CI 1.874-25.849), respectively. Many studies state that preterm birth is a consequence of multifactorial factors.…”
Section: Discussionmentioning
confidence: 64%
“…Release of corticotropin-releasing hormone (CRH) by the placenta can affect gestational duration which is a risk for preterm birth. It is not just hormones, Saleha et al 19 and Primawati et al 20 stated that maternal stress levels during pregnancy have influenced by other factors such as job, parity, social economic factors, social support, and environment. There is a significant association between maternal jobs and stress levels during pregnancy.…”
Section: Results Andmentioning
confidence: 99%
“…The evaluation scoring is 0 for none or never, 1 for sometimes, 2 for often, and 3 for almost every time. Furthermore, the evaluation indicators of stress levels depend on the score of the sum result in each statement that is normal (0-14), mild (15)(16)(17)(18), moderate (19)(20)(21)(22)(23)(24)(25), severe (26)(27)(28)(29)(30)(31)(32)(33), and very severe (>34). Data collection used an online form called Zoho Survey.…”
Section: Methodsmentioning
confidence: 99%